2008
DOI: 10.1016/j.ejcts.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive mitral valve repair for mitral regurgitation: results of 1339 consecutive patients☆

Abstract: Minimal invasive MV repair, along with certain concomitant procedures, can be performed in the vast majority of patients with MR. Our large series demonstrates that these procedures can be performed with low perioperative complication rates and very good durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(206 citation statements)
references
References 18 publications
7
193
1
5
Order By: Relevance
“…They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000). Moreover, we excluded 12 studies because they had no control groups (Loulmet et al, 1998;Mishra et al, 1999;Riess et al, 2001;Grossi et al, 2002;Onnasch et al, 2002b;Aybek et al, 2006;Martin et al, 2006;Seeburger et al, 2008;Glaubera et al, 2009;Müller et al, 2011;Reser et al, 2012), which ranged from 22 to 1339 in sample size. However, these studies, with 3085 patients in total, summarized the long-term clinical experience of ALMT, which is useful for making clinical decisions and ensuring the safety of ALMT.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000). Moreover, we excluded 12 studies because they had no control groups (Loulmet et al, 1998;Mishra et al, 1999;Riess et al, 2001;Grossi et al, 2002;Onnasch et al, 2002b;Aybek et al, 2006;Martin et al, 2006;Seeburger et al, 2008;Glaubera et al, 2009;Müller et al, 2011;Reser et al, 2012), which ranged from 22 to 1339 in sample size. However, these studies, with 3085 patients in total, summarized the long-term clinical experience of ALMT, which is useful for making clinical decisions and ensuring the safety of ALMT.…”
Section: Discussionmentioning
confidence: 99%
“…Mitral, tricuspid, and atrial surgery, including valve pathology, left and right cardiac masses and inter-atrial septum defects have been for many years corrected by right mini-thoracotomy in selected centers (4,5). Worldwide experience with these techniques has been growing, and results have progressively shown this approach is equal, if not better, to standard sternotomy in this setting.…”
Section: Mitral Tricuspid and Atrial Surgerymentioning
confidence: 99%
“…12,13 The minimally invasive technique for MV and TV surgery via a right anterolateral mini-thoracotomy has been described earlier by our group. [14][15][16][17] The technique of MV repair/replacement and the decision for or against additional TV repair was at the surgeon's discretion, depending on the preoperative and/or intraoperative echocardiography data.…”
Section: Methodsmentioning
confidence: 99%